National identity in psychology students: Analysis in a national university and a private university in Lima - De La Cruz, Carlos (2014)
We analyzed national identity in Psychology students from a national university and a private university. The CAS Inventory (Cognitive, Affective and Social) for National Identity by Salgado (2010) was used. It is a psychometrically evaluated instrument for validity and reliability, which was applied to a sample of 200 psychology students (UCV = 100 and UNFV = 100) who were randomly selected in a simple probabilistic way. The results, in total averages and CAS areas, showed highly significant differences (p < 0,01) between both groups. They were favorable for UNFV students, although they showed only slightly favorable (21.5%) levels. Also, in terms of origin, there are significant differences (p < 0,01), showing higher favorable values in students from provincial. According to religion, values denote similarity with no significant differences.